Dynamical heterogeneities in glasses, colloids, and granular media - Berthier, Ludovic (Oxford : Oxford University Press, 2011)
Most everyday solid materials, from plastics to cosmetic gels exist in a non-crystalline, amorphous form: they are glasses. Yet we are still seeking an explanation as to what glasses really are and to why they form. Here, leading experts present broad perspectives on one of the deepest mysteries of condensed matter physics.
Includes bibliographical references.
Description based on print version record.
Keywords: Glass; Colloids; Granular materials